2016
DOI: 10.3389/fmicb.2016.00919
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Side of the Mushroom Spring Microbial Mat: Life in the Shadow of Chlorophototrophs. I. Microbial Diversity Based on 16S rRNA Gene Amplicons and Metagenomic Sequencing

Abstract: Microbial-mat communities in the effluent channels of Octopus and Mushroom Springs within the Lower Geyser Basin at Yellowstone National Park have been studied for nearly 50 years. The emphasis has mostly focused on the chlorophototrophic bacterial organisms of the phyla Cyanobacteria and Chloroflexi. In contrast, the diversity and metabolic functions of the heterotrophic community in the microoxic/anoxic region of the mat are not well understood. In this study we analyzed the orange-colored undermat of the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
115
3
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(138 citation statements)
references
References 126 publications
(251 reference statements)
17
115
3
3
Order By: Relevance
“…As noted above, the composition and diversity of the undermat was described in a previous report (Thiel et al, 2016). In this report, we focus on a description of the metabolic potentials and hypothesized interactions among mat community members.…”
Section: Introductionmentioning
confidence: 52%
“…As noted above, the composition and diversity of the undermat was described in a previous report (Thiel et al, 2016). In this report, we focus on a description of the metabolic potentials and hypothesized interactions among mat community members.…”
Section: Introductionmentioning
confidence: 52%
“…The Anaerolineae have generally been isolated as obligately anaerobic heterotrophs (e.g., Sekiguchi et al, 2003;Yamada et al, 2006), but genome sequencing has revealed the capacity for aerobic respiration in diverse members of this clade (e.g., Pace, Hemp, Ward, & Fischer, 2015;. Furthermore, a genome for an organism closely related to the Anaerolineae with genes for photosynthesis has been assembled from a Yellowstone National Park metagenome (Klatt et al, 2011;Tank, Thiel, Ward, & Bryant, 2017;Thiel et al, 2016 (Podosokorskaya, Bonch-Osmolovskaya et al, 2013;Yamada et al, 2007).…”
mentioning
confidence: 99%
“…To analyze microbial diversity, 16S rRNA amplicon‐based sequencing has been widely used in various engineered or environmental samples (Hess et al., ; Singh et al., ; Chan et al., ; Mhuantong, Charoensawan, Kanokratana, Tangphatsornruang, & Champreda, ; Vishnivetskaya et al., ). Culture independent studies at hot springs in YNP have a long research history where the clonal library was initially used (Brock, ; Thiel et al., ). Microbial diversity in Octopus and Mushroom Springs at YNP were revisited using high‐throughput NGS (Thiel et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Culture independent studies at hot springs in YNP have a long research history where the clonal library was initially used (Brock, ; Thiel et al., ). Microbial diversity in Octopus and Mushroom Springs at YNP were revisited using high‐throughput NGS (Thiel et al., ). Most of the studied hot springs lack lignocellulosic plant materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation